Wear-resistant alloy and preparation method and application thereof

By optimizing the chemical composition and heat treatment process of wear-resistant alloys, bainite + residual austenite structure is formed, which solves the problem of insufficient wear resistance and toughness of blades of agricultural rice cutting machines, and achieves efficient and low-cost alloy manufacturing and use effects.

CN120249814APending Publication Date: 2025-07-04DONGGUAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510414664.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The blades of existing agricultural rice harvesters are easily damaged when cutting harder rice poles. They urgently need to improve toughness and strength, enhance wear resistance to increase the number of cutting times, and strive to reduce costs. The existing heat treatment methods have problems such as uneven performance and high cost during too long.

Method used

Wear-resistant alloys with specific chemical components are adopted, including Cr: 0.5% to 1.0%, Mn: 0.5% to 1.0%, Ti: 0.05% to 0.1%, Si: 1.6% to 2.7%, C: 0.6% to 1.0%, Mo: 0.004% to 0.01%. By optimizing the heat treatment process, the isothermal transition time is shortened, and primary isothermal treatment and grading quenching technology are used to form bainite + residual austenite structure to reduce carbide generation.

Benefits of technology

The high wear resistance and toughness of the alloy is achieved, which reduces production costs, shortens the manufacturing cycle, improves the overall performance of the alloy, reduces the material loss rate, and improves the service life of the blade.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120249814A_ABST
    Figure CN120249814A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy production, in particular to a wear-resistant alloy as well as a preparation method and application thereof, and the wear-resistant alloy comprises the following chemical components in percentage by weight: 0.5%-1.0% of Cr, 0.5%-1.0% of Mn, 0.05%-0.1% of Ti, 1.6%-2.7% of Si, 0.6%-1.0% of C, 0.004%-0.01% of Mo and the balance of Fe and inevitable impurities. Wherein C / Cr is less than 1%, and Mn + Cr is less than 1.6%. According to the method, the economical efficiency is guaranteed, meanwhile, the overall performance can be guaranteed through heat treatment, the isothermal transformation time is shortened, and the mechanical property and the wear resistance of the alloy are comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloy production, and in particular to a wear-resistant alloy, a preparation method and an application of the alloy. Background Art

[0002] Existing blades of agricultural rice harvesters are easily damaged when cutting relatively hard rice straws. There is an urgent need to improve toughness and strength, enhance wear resistance to increase the number of cuts, and at the same time strive to reduce costs. Even in the event of shutdown, blade damage, etc., expenses can be controlled to the greatest extent. By using the isothermal heat preservation method for treatment, the batch manufacturing rate is fast and the cycle is short, and it has good strength, hardness, toughness, and impact wear resistance.

[0003] Chinese Patent CN118814091A discloses a high-strength high-carbon bainite wear-resistant steel and a preparation method thereof. After austenitization, it is isothermally held at 230 - 300°C for 6 - 12 h, which takes too long and has poor economy. And long-time heat preservation will make the tissue distribution uneven and the performance difference large. According to JMatpro analysis, it is found that the bainite finishing time in this heat treatment does not exceed 10000 s, that is, 2.7 h. Although too long heat treatment time can refine bainite grains, at the same time, the stability of retained austenite decreases. Retained austenite can produce the Trip effect under high impact loads, which is not conducive to the overall wear resistance of the steel. At the same time, too long heat preservation time will precipitate carbides such as Mn and Cr, resulting in a decrease in the overall strength, plasticity and toughness of the steel.

[0004] Chinese Patent CN112695253B discloses a carbide-containing high-strength and high-toughness bainite wear-resistant steel and a preparation method thereof. Its preparation process also has the problem of too long heat preservation time and inability to achieve the balance between bainite and retained austenite.

[0005] Therefore, to meet the alloy properties with good strength, hardness, toughness, and impact wear resistance, and shorten the batch manufacturing cycle, further research and innovation are needed. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a wear-resistant alloy, a preparation method and an application of the alloy, which can ensure economy and at the same time ensure the overall performance through heat treatment, shorten the isothermal transformation time, and comprehensively improve the mechanical properties and wear resistance of the alloy.

[0007] To solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A wear-resistant alloy, the chemical composition of the alloy by weight percentage includes: Cr: 0.5% - 1.0%, Mn: 0.5% - 1.0%, Ti: 0.05% - 0.1%, Si: 1.6% - 2.7%, C: 0.6% - 1.0%, Mo: 0.004% - 0.01%, the balance is Fe and unavoidable impurities; wherein, C / Cr < 1%, Mn + Cr < 1.6%.

[0009] Preferably, the pearlite lamellar spacing of the alloy is 140 nm - 250 nm.

[0010] Preferably, the tensile properties of the alloy in the as-received state are: tensile strength of 1200 MPa - 1300 MPa; yield strength of 700 MPa - 800 MPa; elongation after fracture of 5% - 8%; surface Vickers hardness of 370 HV - 400 HV; core Vickers hardness of 380 HV - 420 HV.

[0011] Preferably, the alloy has a Rockwell hardness > 55 HRC, a retained austenite content > 10%, and an impact wear loss of < 0.92 g for 2 h - 4 J in the as-received state.

[0012] Preferably, the matrix metallographic structure of the alloy after heat treatment consists of bainitic ferrite + retained austenite, and the carbide is circular titanium carbide with a size of 10 nm - 30 nm.

[0013] The preparation method of a wear-resistant alloy according to any one of the above, comprising the following steps:

[0014] S1, placing the raw materials in a vacuum induction melting furnace, heating to 1580 °C - 1620 °C for melting under an argon protective atmosphere, and casting into a graphite mold at a cooling rate of 20 °C - 30 °C / s after the alloy composition is uniform to obtain a square ingot with a diameter of 200 mm - 290 mm;

[0015] S2, placing the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heating to 1150 °C - 1250 °C at a rate of 80 - 100 °C / h, introducing a CO2 + NH3 mixed protective gas, and holding for 10 h - 12 h; after completion of diffusion annealing, cooling with the furnace to 1050 °C - 1100 °C at a rate of 15 - 20 °C / min, immediately transferring to a high-speed forging press for multi-directional forging, controlling the single-pass reduction to be 25 - 30% and the cumulative deformation to be ≥ 70%, and monitoring the forging process in real time with an infrared thermometer, stopping forging when the surface temperature of the billet drops to 950 °C - 1020 °C, and air-cooling the obtained forging billet to room temperature at a cooling rate of ≥ 50 °C / s under forced air cooling conditions;

[0016] S3. Using wire cutting technology, the forging blank obtained in S2 is precisely cut into a cuboid specimen of 10 mm × 70 mm × 80 mm, placed in a salt bath furnace and heated to 900 °C - 950 °C for 30 min - 35 min of heat preservation, and then transferred to a constant temperature circulating water bath for step quenching: in the first stage, water quenching is carried out at a cooling rate of 20 - 25 °C / s to 290 °C - 310 °C, and immediately transferred to a tempering furnace to be heated to 270 °C - 310 °C at a rate of 5 - 8 °C / min for 1 h - 1.5 h of heat preservation. In the second stage, rapid water quenching is carried out using a 10% NaCl aqueous solution (20 - 25 °C), and the transfer time is controlled within 3 s, and finally cooled to room temperature.

[0017] Preferably, in step S1, the volume ratio of CO2 to NH3 is 3:1.

[0018] Preferably, in step S3, the cuboid steel has its length direction perpendicular to the water surface, the distance between the steel cross-section and the water surface > 10 mm, and the temperature of the quenching medium is 70 °C - 80 °C.

[0019] Preferably, in step S3, the water quenching time is 6 - 20 s, the number of continuous water quenching times is 2 - 4 times. Each time it is taken out, the temperature needs to be detected by an infrared temperature detector, the inclination angle of the probe measurement is 120° - 150°, the temperature of the first water quenching ≤ 550 °C, the temperature of the second water quenching ≤ 400 °C. When water quenched to 330 °C - 360 °C, it is air-cooled to 270 °C - 310 °C and then put into a heating furnace for heat preservation.

[0020] The application of a wear-resistant alloy according to any one of the above, and this alloy is applied to the blade of an agricultural rice harvester, specifically the moving blade of a reciprocating cutter.

[0021] The beneficial effects of the present invention:

[0022] 1. The present invention optimizes and innovates the alloy formula, specifically as follows: ① Since when the C content is greater than 0.6%, an Mn content exceeding 1.5% will greatly increase the brittleness of the steel, we reduce the Mn content to below 0.5 - 1% to ensure economy and also optimize the overall performance through heat treatment; ② Using Ti to replace some precious metal elements such as Cr and Ni, while ensuring the element ratio, makes it so that Mn and Cr hardly form carbides. Adding a small amount of Ti, its main function is that TiC formed during solidification in the casting process dissolves in the matrix to enhance wear resistance. If the Ti content in conventional alloys is too high, it will cause the matrix hardness to decrease, the wear resistance to become poor, and the toughness and plasticity to also become poor. Therefore, through reasonable component matching design in the present invention, the dosage is controlled at 0.05% - 0.1%, combined with the preparation process, to ensure the excellent comprehensive performance of this alloy; ③ Increasing the Si content to 1.6% - 2.7% (the conventional setting in the prior art is 0.6% - 1.0%) strongly inhibits the precipitation of cementite and promotes the formation of carbide-free bainite; ④ Designing an ultra-low content of Mo (0.004% - 0.01%) to regulate the bainite phase transformation kinetics, shortening the isothermal transformation time to 30 - 50 min (the conventional value in the prior art is ≥90 min); ⑤ Compared with the prior art, the present invention reduces the use of elements AI, Ni, and rare earth Ce, and has a low Mn content, adding a small amount of Ti, making the cost lower, and also enabling the Rockwell hardness of the alloy to be >55 HV and the retained austenite content to be >10%.

[0023] 2. When preparing the alloy, the present invention optimizes the heat treatment process, shortens the bainitization time, and achieves better results in only 1 h compared to the 6 h heat preservation process in the prior art.

[0024] 3. In step S3 of the present invention, one-time isothermal treatment is adopted, without the complicated heating and cooling, optimizing the complicated quenching steps in the prior art. Only by quenching to above 270°C once can the heat preservation temperature range be ensured, avoiding the adverse effects on toughness caused by the formation of martensite structure at low temperature and the problem of reduced RA content.

[0025] 4. The alloy of the present invention has an ultra-high hardness of up to 55 HRC in the case of bainite + retained austenite and a small amount of TiC, and in the wear resistance experiment, the impact wear loss is less than that of the martensite + bainite + retained austenite composite structure, and the measured matrix mass loss rate is reduced by 15% - 20%. The conventional bainite + martensite recurrence structure relies on second-phase particles + dislocation strengthening, while the present invention mainly relies on interface strengthening + TRIP effect synergy. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 are the XRD diagram and SEM diagram of the present invention;

[0027] Figure 2 is an example of the SEM diagram of the prior art;

[0028] Figure 3 It is the isothermal treatment bainitization process diagram of the present invention;

[0029] Figure 4 It is the thermal expansion amount and time diagram for completing bainite transformation of the present invention;

[0030] Figure 5 It is the SEM diagram of impact wear of bainite + retained austenite composite phase of the present invention;

[0031] Figure 6 It is the SEM diagram of impact wear of martensite + bainite + retained austenite composite phase for comparing with the prior art of the present invention;

[0032] Figure 7 It is the XRD diagram and SEM diagram for comparative testing when quenching below 250°C of the present invention. Detailed implementation manners

[0033] For the convenience of understanding by those skilled in the art, the present invention will be further described below in conjunction with embodiments and the accompanying drawings. The content mentioned in the implementation manners does not limit the present invention.

[0034] Embodiment 1

[0035] Prepare raw materials according to the following weight ratio:

[0036] C: 0.65%, Mn: 0.78%, Cr: 0.79%, Si: 1.8%, Ti: 0.05%, Mo: 0.006%, and the balance is Fe and unavoidable impurities.

[0037] Prepare the alloy:

[0038] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580°C - 1620°C for melting under an argon protection atmosphere. After the alloy composition is uniform, cast them into a graphite mold at a cooling rate of 20°C - 30°C / s to form a square ingot with a diameter of 213 mm;

[0039] S2. Place the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1200°C at a rate of 80 - 100°C / h, introduce a CO2 + NH3 mixed protective gas, and the volume ratio of CO2 to NH3 is 3:1, and keep it warm for 11 h; after completing the diffusion annealing, cool it in the furnace at a rate of 15 - 20°C / min to 1060°C, immediately transfer it to a high-speed forging press for multi-directional forging, control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. The forging process is monitored in real time by an infrared thermometer. Stop forging when the surface temperature of the billet drops to 990°C. The obtained forged billet is air-cooled to room temperature at a cooling rate of ≥ 50°C / s under forced air cooling conditions;

[0040] S3. Using wire cutting technology, the forging blank obtained in S2 is precisely cut into a cuboid specimen of 10 mm×70 mm×80 mm, placed in a salt bath furnace and heated to 900 °C for insulation for 30 min to 35 min, and then transferred to a constant temperature circulating water bath for step quenching: in the first stage, water quenching is carried out at a cooling rate of 20 - 25 °C / s to 294 °C, and immediately transferred to a tempering furnace and heated to 270 °C at a rate of 5 - 8 °C / min for insulation for 1.1 h. Among them, the cuboid steel is immersed vertically in the quenching medium in the length direction, so that its cross-section is parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface is > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium; in the first stage, pre-cooling treatment is carried out with a constant temperature quenching medium of 70 °C - 80 °C, and in the second stage, it is switched to a 10% NaCl aqueous solution at 20 - 25 °C for intermittent rapid quenching: the duration of each quenching is 6 - 20 s, and the cyclic operation is carried out 2 - 4 times; after each quenching, an infrared thermometer is used to detect the temperature, and the measuring axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. After the first quenching, the temperature of the workpiece is ≤ 550 °C, and after the second quenching, the temperature is ≤ 400 °C; finally, quenching is stopped after cooling to 330 °C - 360 °C, and air-cooled to 270 °C - 310 °C and then transferred to a heating furnace for insulation treatment. The transfer time is controlled within 3 s, and finally cooled to room temperature to obtain the alloy.

[0041] The Rockwell hardness of this alloy is 56.6 HRC, the impact toughness is 14.1 J / cm2, the impact wear amount is 0.91 g, and the retained austenite content is 10.3%.

[0042] Example 2

[0043] Prepare raw materials according to the following weight ratio:

[0044] C: 0.55%, Mn: 0.78%, Cr: 0.72%, Si: 2.4%, Ti: 0.05%, Mo: 0.009%, and the balance is Fe and inevitable impurities.

[0045] Prepare the alloy:

[0046] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580 °C - 1620 °C for melting under an argon protection atmosphere. After the alloy composition is uniform, cast it into a graphite mold at a cooling rate of 20 °C - 30 °C / s to form a square ingot with a diameter of 243 mm;

[0047] S2. Place the square ingot obtained in S1 into a gradient temperature-controlled diffusion annealing furnace, heat it to 1200 °C at a rate of 80 - 100 °C / h, introduce a mixed protective gas of CO2 + NH3 with a volume ratio of CO2 to NH3 of 3:1, and hold for 11 h. After completion of diffusion annealing, cool it in the furnace to 1060 °C at a rate of 15 - 20 °C / min, immediately transfer it to a high-speed forging press for multi-directional forging, control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer for real-time monitoring, and stop forging when the surface temperature of the billet drops to 1000 °C. The obtained forged billet is air-cooled to room temperature under forced air cooling conditions at a cooling rate ≥ 50 °C / s;

[0048] S3. Use wire cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10 mm × 70 mm × 80 mm, place it in a salt bath furnace and heat it to 900 °C and hold for 30 - 35 min, then transfer it to a constant temperature circulating water bath for step quenching: In the first stage, water quench at a cooling rate of 20 - 25 °C / s to 292 °C, immediately transfer it to a tempering furnace and heat it to 270 °C at a rate of 5 - 8 °C / min and hold for 1.2 h. Among them, the cuboid steel is vertically immersed in the quenching medium in the length direction, making its cross-section parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium. In the first stage, use a constant temperature quenching medium of 70 - 80 °C for pre-cooling treatment, and in the second stage, switch to a 10% NaCl aqueous solution at 20 - 25 °C for intermittent rapid quenching: The single quenching duration is 6 - 20 s, and the cyclic operation is 2 - 4 times; After each quenching, use an infrared thermometer to detect the temperature, and the measuring axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. After the first quenching, the workpiece temperature ≤ 550 °C, and after the second quenching, the temperature ≤ 400 °C; Finally, stop quenching after cooling to 330 - 360 °C, air-cool to 270 - 310 °C and transfer it to a heating furnace for heat preservation treatment, and control the transfer time within 3 s. Finally, cool to room temperature to obtain the alloy.

[0049] The Rockwell hardness of this alloy is 55.2 HRC, the impact toughness is 15.6 J / cm2, the impact wear amount is 0.92 g, and the retained austenite content is 10.1%.

[0050] Example 3

[0051] Prepare raw materials according to the following weight ratio:

[0052] C: 0.78%, Mn: 0.76%, Cr: 0.81%, Si: 2.7%, Ti: 0.06%, Mo: 0.006%, and the balance is Fe and unavoidable impurities.

[0053] Prepare the alloy:

[0054] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580 °C - 1620 °C for melting under an argon protective atmosphere. After the alloy composition is uniform, cast them into a graphite mold at a cooling rate of 20 °C - 30 °C / s to form a square ingot with a diameter of 233 mm.

[0055] S2. Place the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1200 °C at a rate of 80 - 100 °C / h, introduce a CO2 + NH3 mixed protective gas with a volume ratio of CO2 to NH3 of 3:1, and hold for 11 h. After the diffusion annealing is completed, cool it in the furnace at a rate of 15 - 20 °C / min to 1070 °C, and immediately transfer it to a high-speed forging press for multi-directional forging. Control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer to monitor in real time. Stop forging when the surface temperature of the billet drops to 965 °C. The obtained forged billet is air-cooled to room temperature at a cooling rate of ≥ 50 °C / s under forced air cooling conditions.

[0056] S3. Use wire cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10 mm × 70 mm × 80 mm, place it in a salt bath furnace and heat it to 900 °C for 30 min - 35 min, and then transfer it to a constant temperature circulating water bath for step quenching: In the first stage, quench it in water at a cooling rate of 20 - 25 °C / s to 301 °C, and immediately transfer it to a tempering furnace and heat it to 280 °C at a rate of 5 - 8 °C / min and hold for 1.1 h. Among them, the cuboid steel is immersed vertically in the quenching medium with its cross-section parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface is > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium. In the first stage, use a constant temperature quenching medium of 70 °C - 80 °C for pre-cooling treatment, and in the second stage, switch to a 10% NaCl aqueous solution at 20 - 25 °C for intermittent rapid quenching: The single quenching duration is 6 - 20 s, and the cyclic operation is 2 - 4 times; After each quenching, use an infrared thermometer to detect the temperature, and the measuring axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. After the first quenching, the temperature of the workpiece is ≤ 550 °C, and after the second quenching, the temperature is ≤ 400 °C; Finally, stop quenching after cooling to 330 °C - 360 °C, air-cool to 270 °C - 310 °C and transfer it to a heating furnace for heat preservation treatment, and control the transfer time within 3 s. Finally, cool it to room temperature to obtain the alloy.

[0057] The Rockwell hardness of this alloy is 58.1 HRC, the impact toughness is 14.9 J / cm2, the impact wear amount is 0.87 g, and the retained austenite content is 10.6%.

[0058] Example 4

[0059] Prepare raw materials according to the following weight ratio:

[0060] C: 0.74%, Mn: 0.71%, Cr: 0.88%, Si: 1.9%, Ti: 0.06%, Mo: 0.007%, the balance being Fe and unavoidable impurities.

[0061] Prepare the alloy:

[0062] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580 °C - 1620 °C for melting under an argon protective atmosphere, and pour them into a graphite mold for shaping at a cooling rate of 20 °C - 30 °C / s after the alloy composition is uniform, obtaining an ingot with a diameter of 264 mm.

[0063] S2. Place the ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1200 °C at a rate of 80 - 100 °C / h, introduce a CO2 + NH3 mixed protective gas with a volume ratio of CO2 to NH3 of 3:1, and hold for 11 h. After the diffusion annealing is completed, cool it down to 1080 °C with the furnace at a rate of 15 - 20 °C / min, and immediately transfer it to a high-speed forging press for multi-directional forging. Control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer to monitor in real time. Stop forging when the surface temperature of the billet drops to 1020 °C. Air-cool the obtained forged billet to room temperature at a cooling rate of ≥ 50 °C / s under forced air cooling conditions.

[0064] S3. Use wire cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10 mm × 70 mm × 80 mm, place it in a salt bath furnace and heat it to 900 °C for 30 min - 35 min, and then transfer it to a constant temperature circulating water bath for step quenching: In the first stage, quench it in water at a cooling rate of 20 - 25 °C / s to 308 °C, and immediately transfer it to a tempering furnace and heat it to 280 °C at a rate of 5 - 8 °C / min and hold for 1.4 h. Among them, the cuboid steel is vertically immersed in the quenching medium with its cross-section parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium. In the first stage, use a 70 °C - 80 °C constant temperature quenching medium for pre-cooling treatment, and in the second stage, switch to a 10% NaCl aqueous solution at 20 - 25 °C for intermittent rapid quenching: The single quenching duration is 6 - 20 s, and the cycle operation is 2 - 4 times. After each quenching, use an infrared thermometer to detect the temperature, and the measuring axis of the probe forms an angle of 120 ° - 150 ° with the normal line of the workpiece surface. After the first quenching, the workpiece temperature ≤ 550 °C, and after the second quenching, the temperature ≤ 400 °C. Finally, stop quenching when it cools to 330 °C - 360 °C, air-cool it to 270 °C - 310 °C and transfer it to a heating furnace for heat preservation treatment, and control the transfer time within 3 s. Finally, cool it to room temperature to obtain the alloy.

[0065] The Rockwell hardness of this alloy is 56.5 HRC, the impact toughness is 16.1 J / cm2, the impact wear amount is 0.94 g, and the retained austenite content is 11.5%.

[0066] Example 5

[0067] Prepare raw materials according to the following weight ratio:

[0068] C: 0.82%, Mn: 0.68%, Cr: 0.87%, Si: 2.1%, Ti: 0.07%, Mo: 0.006%, and the balance is Fe and inevitable impurities.

[0069] Prepare the alloy:

[0070] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580°C - 1620°C for melting under an argon protective atmosphere. After the alloy composition is uniform, cast it into a graphite mold at a cooling rate of 20°C - 30°C / s to form a square ingot with a diameter of 251 mm.

[0071] S2. Place the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1200°C at a rate of 80 - 100°C / h, introduce a CO2 + NH3 mixed protective gas, with the volume ratio of CO2 to NH3 being 3:1, and hold for 11 h. After the diffusion annealing is completed, cool it in the furnace at a rate of 15 - 20°C / min to 1060°C, and immediately transfer it to a high-speed forging press for multi-directional forging. Control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. The forging process is monitored in real time by an infrared thermometer. Stop forging when the surface temperature of the billet drops to 955°C. The obtained forged billet is air-cooled to room temperature at a cooling rate of ≥ 50°C / s under forced air cooling conditions.

[0072] S3. Using wire cutting technology, the forging blank obtained in S2 is precisely cut into a cuboid specimen of 10 mm × 70 mm × 80 mm, placed in a salt bath furnace and heated to 900 °C for 30 min - 35 min, and then transferred to a constant temperature circulating water bath for step quenching: in the first stage, water quenching is carried out at a cooling rate of 20 - 25 °C / s to 294 °C, and immediately transferred to a tempering furnace and heated to 290 °C at a rate of 5 - 8 °C / min and held for 1.5 h. Among them, the cuboid steel is vertically immersed in the quenching medium in the length direction, so that its cross-section is parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium; in the first stage, pre-cooling treatment is carried out with a constant temperature quenching medium of 70 °C - 80 °C, and in the second stage, intermittent rapid quenching is carried out with a 10% NaCl aqueous solution at 20 - 25 °C: the duration of each quenching is 6 - 20 s, and the cyclic operation is carried out 2 - 4 times; after each quenching, an infrared thermometer is used to detect the temperature, and the measuring axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. After the first quenching, the temperature of the workpiece ≤ 550 °C, and after the second quenching, the temperature ≤ 400 °C; finally, quenching is stopped after cooling to 330 °C - 360 °C, air-cooled to 270 °C - 310 °C and transferred to a heating furnace for heat preservation treatment, and the transfer time is controlled within 3 s, and finally cooled to room temperature to obtain the alloy.

[0073] The Rockwell hardness of this alloy is 57.3 HRC, the impact toughness is 15.3 J / cm2, the impact wear amount is 0.83 g, and the retained austenite content is 11.6%.

[0074] Example 6

[0075] Prepare raw materials according to the following weight ratio:

[0076] C: 0.91%, Mn: 0.52%, Cr: 0.93%, Si: 1.6%, Ti: 0.05%, Mo: 0.008%, and the balance is Fe and inevitable impurities.

[0077] Prepare the alloy:

[0078] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580 °C - 1620 °C for melting under an argon protection atmosphere, and pour them into a graphite mold for forming at a cooling rate of 20 °C - 30 °C / s after the alloy composition is uniform, to obtain a square ingot with a diameter of 284 mm.

[0079] S2. Place the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1200 °C at a rate of 80 - 100 °C / h, introduce a mixed protective gas of CO2 + NH3, with the volume ratio of CO2 to NH3 being 3:1, and hold for 11 h. After completion of diffusion annealing, cool it in the furnace at a rate of 15 - 20 °C / min to 1065 °C, immediately transfer it to a high-speed forging press for multi-directional forging, control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer for real-time monitoring. Stop forging when the surface temperature of the billet drops to 980 °C. Air-cool the obtained forged billet to room temperature at a cooling rate of ≥ 50 °C / s under forced air cooling conditions;

[0080] S3. Use wire cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10 mm × 70 mm × 80 mm, place it in a salt bath furnace and heat it to 900 °C and hold for 30 - 35 min, then transfer it to a constant temperature circulating water bath for step quenching: In the first stage, water quench at a cooling rate of 20 - 25 °C / s to 296 °C, immediately transfer it to a tempering furnace and heat it to 310 °C at a rate of 5 - 8 °C / min and hold for 1.0 h. Among them, the cuboid steel is vertically immersed in the quenching medium in the length direction, making its cross-section parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface > 10 mm, and the immersion depth ensures that the entire workpiece is completely immersed in the medium; In the first stage, use a constant temperature quenching medium of 70 - 80 °C for pre-cooling treatment, and switch to a 10% NaCl aqueous solution at 20 - 25 °C for intermittent rapid quenching in the second stage: The single quenching duration is 6 - 20 s, and the cyclic operation is 2 - 4 times; After each quenching, use an infrared thermometer to detect the temperature, and the measuring axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. The temperature of the workpiece after the first quenching ≤ 550 °C, and the temperature after the second quenching ≤ 400 °C; Finally, stop quenching after cooling to 330 °C - 360 °C, air-cool to 270 °C - 310 °C and transfer it to a heating furnace for heat preservation treatment, and control the transfer time within 3 s. Finally, cool to room temperature to obtain the alloy.

[0081] The Rockwell hardness of this alloy is 56.7 HRC, the impact toughness is 14.4 J / cm2, the impact wear amount is 0.92 g, and the retained austenite content is 10.1%.

[0082] Example 7

[0083] Prepare raw materials according to the following weight ratios:

[0084] C: 0.60%, Mn: 1.00%, Cr: 0.50%, Si: 1.8%, Ti: 0.10%, Mo: 0.010%, and the balance is Fe and unavoidable impurities.

[0085] Prepare the alloy:

[0086] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580 °C - 1620 °C for melting under an argon protective atmosphere. After the alloy composition is uniform, cast them into a graphite mold at a cooling rate of 20 °C - 30 °C / s to form a square ingot with a diameter of 290 mm.

[0087] S2. Place the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1150 °C at a rate of 80 - 100 °C / h, introduce a mixed protective gas of CO2 + NH3, with the volume ratio of CO2 to NH3 being 3:1, and hold for 10 h. After the diffusion annealing is completed, cool it in the furnace to 1100 °C at a rate of 15 - 20 °C / min, and immediately transfer it to a high-speed forging press for multi-directional forging. Control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer to monitor in real time. Stop forging when the surface temperature of the billet drops to 950 °C. The obtained forged billet is air-cooled to room temperature at a cooling rate of ≥ 50 °C / s under forced air cooling conditions.

[0088] S3. Use wire cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10 mm × 70 mm × 80 mm, place it in a salt bath furnace and heat it to 950 °C for 30 min - 35 min, and then transfer it to a constant temperature circulating water bath for step quenching: In the first stage, quench it in water at a cooling rate of 20 - 25 °C / s to 290 °C, and immediately transfer it to a tempering furnace and heat it to 300 °C at a rate of 5 - 8 °C / min and hold for 1.0 h. Among them, the cuboid steel is vertically immersed in the quenching medium with its cross-section parallel to the liquid surface of the medium. After immersion, the height of the lowest point of the cross-section from the liquid surface is > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium. In the first stage, use a constant temperature quenching medium of 70 °C - 80 °C for pre-cooling treatment, and in the second stage, switch to a 10% NaCl aqueous solution at 20 - 25 °C for intermittent rapid quenching: The single quenching duration is 6 - 20 s, and the cyclic operation is 2 - 4 times; after each quenching, use an infrared thermometer to detect the temperature, and the measurement axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. After the first quenching, the workpiece temperature ≤ 550 °C, and after the second quenching, the temperature ≤ 400 °C; finally, stop quenching when it cools to 330 °C - 360 °C, air-cool to 270 °C - 310 °C and transfer it to a heating furnace for heat preservation treatment, and control the transfer time within 3 s. Finally, cool it to room temperature to obtain the alloy.

[0089] The Rockwell hardness of this alloy is 55.0 HRC, the impact toughness is 14.0 J / cm2, the impact wear amount is 0.91 g, and the retained austenite content is 10.0%.

[0090] Example 8

[0091] Prepare raw materials according to the following weight ratios:

[0092] C: 1.00%, Mn: 0.50%, Cr: 1.00%, Si: 2.2%, Ti: 0.07%, Mo: 0.004%, the balance being Fe and inevitable impurities.

[0093] Prepare the alloy:

[0094] S1. Place the raw materials in a vacuum induction melting furnace, heat them to 1580°C - 1620°C for melting under an argon protection atmosphere, and pour them into a graphite mold for forming at a cooling rate of 20°C - 30°C / s after the alloy composition is uniform, obtaining a square ingot with a diameter of 200 mm.

[0095] S2. Place the square ingot obtained in S1 in a gradient temperature-controlled diffusion annealing furnace, heat it to 1250°C at a rate of 80 - 100°C / h, introduce a CO2 + NH3 mixed protective gas with a volume ratio of CO2 to NH3 of 3:1, and hold for 12 h. After completion of diffusion annealing, cool it in the furnace to 1050°C at a rate of 15 - 20°C / min, immediately transfer it to a high-speed forging press for multi-directional forging, control the single-pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer to monitor in real time, and stop forging when the surface temperature of the billet drops to 950°C. The obtained forged billet is air-cooled to room temperature at a cooling rate of ≥ 50°C / s under forced air cooling conditions.

[0096] S3. Use wire cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10 mm × 70 mm × 80 mm, place it in a salt bath furnace and heat it to 950°C for 30 min - 35 min, and then transfer it to a constant temperature circulating water bath for step quenching: In the first stage, quench it in water at a cooling rate of 20 - 25°C / s to 310°C, immediately transfer it to a tempering furnace and heat it to 290°C at a rate of 5 - 8°C / min and hold for 1.0 h. Among them, the cuboid steel is vertically immersed in the quenching medium in the length direction, making its cross-section parallel to the liquid level of the medium. After immersion, the height of the lowest point of the cross-section from the liquid level > 10 mm, and the immersion depth ensures that the whole workpiece is completely immersed in the medium. In the first stage, use a 70°C - 80°C constant temperature quenching medium for pre-cooling treatment, and in the second stage, switch to a 10% NaCl aqueous solution at 20 - 25°C for intermittent rapid quenching: The single quenching duration is 6 - 20 s, and the cyclic operation is carried out 2 - 4 times. After each quenching, use an infrared thermometer to detect the temperature, and the measuring axis of the probe forms an angle of 120° - 150° with the normal line of the workpiece surface. After the first quenching, the temperature of the workpiece ≤ 550°C, and after the second quenching, the temperature ≤ 400°C. Finally, stop quenching after cooling to 330°C - 360°C, air-cool to 270°C - 310°C and transfer it to a heating furnace for heat preservation treatment, and control the transfer time within 3 s, and finally cool to room temperature to obtain the alloy.

[0097] The Rockwell hardness of this alloy is 57.2 HRC, the impact toughness is 14.4 J / cm2, the impact wear amount is 0.88 g, and the retained austenite content is 11.2%.

[0098] The present invention optimizes and innovates the alloy formula, specifically: ① Since when the C content is greater than 0.6%, the Mn content exceeding 1.5% will greatly increase the brittleness of the steel, so we reduce the Mn content to below 0.5 - 1%, ensuring economy and also being able to optimize the overall performance through heat treatment; ② Using Ti to replace part of the precious metal elements such as Cr and Ni, while ensuring the element ratio, makes it almost impossible for Mn and Cr to form carbides. Adding a small amount of Ti, its main function is that TiC formed during solidification in the casting process dissolves in the matrix to enhance wear resistance. If the Ti content in the conventional alloy is too high, it will lead to a decrease in matrix hardness, poor wear resistance, and also poor toughness and plasticity. Therefore, through reasonable component matching design in the present invention, the dosage is controlled within 0.05% - 0.1%, combined with the preparation process to ensure excellent comprehensive performance of this alloy; ③ Increasing the Si content to 1.6% - 2.7% (the conventional setting in the prior art is 0.6% - 1.0%), strongly inhibiting the precipitation of cementite and promoting the formation of carbide-free bainite; ④ Designing an ultra-low content of Mo (0.004% - 0.01%) to regulate the bainite phase transformation kinetics, shortening the isothermal transformation time to 30 - 50 min (the conventional in the prior art is ≥90 min); ⑤ Compared with the prior art, the present invention reduces the use of elements AI, Ni, and rare earth Ce, and has a low Mn content, adding a small amount of Ti, making the cost lower, and also enabling the Rockwell hardness of the alloy to be >55 HV and the retained austenite content to be >10%. The XRD pattern and SEM image are as Figure 1 shown; while the SEM image of the prior art is as Figure 2 shown, the bainite is thick and large, and the retained austenite is in large blocks, accompanied by a large amount of carbide precipitation.

[0099] When preparing the alloy, the present invention optimizes the heat treatment process, shortens the bainitization time, and achieves better results in only 1 h than the 6 h heat preservation process in the prior art, as Figure 4 shown.

[0100] The present invention adopts one-time isothermal treatment (as Figure 3 shown), without the complicated heating and cooling, optimizing the complicated quenching steps in the prior art. Only by quenching to above 270℃ once can the heat preservation temperature range be ensured, avoiding the problem that the formation of martensite structure at low temperature has an adverse effect on toughness and the RA content decreases. Comparative test: When quenching to below 270℃, martensite structure will be generated, which has an adverse effect on toughness and the RA content decreases, as Figure 7 shown. When the final quenching cooling temperature is controlled below 250℃, the film-like RA almost completely disappears.

[0101] The alloy of the present invention adopts bainite + retained austenite. After 2 hours of wear, a piled-up layer still remains to cover the surface, indicating that the steel can absorb energy through deformation, reduce the direct contact between abrasive grains and the matrix, delay crack propagation, and reduce the material loss rate (as Figure 5 shown. The figure shows the bainite + retained austenite composite phase. After 2 hours of wear, a thick and large piled-up layer still covers the surface, effectively reducing the direct contact between abrasive grains and the matrix, delaying the crack propagation process, thereby significantly reducing the material loss rate and ensuring that the alloy quality will not be lost due to spalling). Combined with a small amount of TiC, it has an ultra-high hardness of up to 55 HRC. And in the wear resistance experiment, the wear amount of impact wear is less than that of the martensite + bainite + retained austenite composite structure (for the martensite + bainite + retained austenite composite structure, without a piled-up layer, it lacks the ability of plastic deformation. Repeated impacts cause the piled-up layer to fall off. Coupled with low toughness, cracks rapidly expand, turning into fatigue spalling and aggravating wear, as Figure 6 shown. The figure shows the martensite + bainite + retained austenite composite phase. After impact wear, it presents morphological features of a large number of cracks and no piled-up layer at the end of the plow groove, lacking the ability of plastic deformation. Repeated impacts cause the surface layer material to fall off; in addition, the toughness of the composite phase is insufficient, and cracks rapidly expand under the action of stress and turn into fatigue spalling, aggravating the phenomenon of matrix mass loss). The measured matrix mass loss rate is reduced by 15% - 20%. The conventional bainite + martensite reproduced structure relies on second-phase particles + dislocation strengthening, while the present invention mainly relies on interface strengthening + TRIP effect synergy.

[0102] All technical features in this embodiment can be modified in appearance according to actual needs.

[0103] The above embodiments are the preferred implementation solutions of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious replacement without departing from the concept of the technical solution of the present invention is within the protection scope of the present invention.

Claims

1. A wear-resistant alloy, characterized in that: The chemical composition of the alloy by weight percentage includes: Cr: 0.5% - 1.0%, Mn: 0.5% - 1.0%, Ti: 0.05% - 0.1%, Si: 1.6% - 2.7%, C: 0.6% - 1.0%, Mo: 0.004% - 0.01%, and the balance is Fe and inevitable impurities; Among them, C / Cr < 1%, Mn + Cr < 1.6%.

2. The wear-resistant alloy according to claim 1, characterized in that: The pearlite lamellar spacing of this alloy is 140nm - 250nm.

3. A wear-resistant alloy according to claim 1, characterized in that: The tensile properties of this alloy in the as - received state are: tensile strength is 1200MPa - 1300MPa; yield strength is 700MPa - 800MPa; elongation after fracture is 5% - 8%; surface Vickers hardness is 370HV - 400HV; core Vickers hardness is 380HV - 420HV.

4. A wear-resistant alloy according to claim 1, characterized in that: This alloy in the as - received state has Rockwell hardness > 55HRC, retained austenite content > 10%, and 2h - 4J impact wear amount < 0.92g.

5. A wear-resistant alloy according to claim 1, characterized in that: After heat treatment, the matrix metallographic structure of this alloy consists of bainitic ferrite + retained austenite, and the carbide is circular titanium carbide with a size of 10nm - 30nm.

6. The preparation method of a wear-resistant alloy according to any one of claims 1-5, characterized in that: It includes the following steps: S1, Place the raw materials in a vacuum induction melting furnace, heat to 1580℃ - 1620℃ for melting under an argon - protective atmosphere. After the alloy composition is uniform, cast it into a graphite mold at a cooling rate of 20℃ - 30℃ / s to form a square ingot with a diameter of 200mm - 290mm; S2, Place the square ingot obtained in S1 in a gradient - temperature - controlled diffusion annealing furnace, heat it to 1150℃ - 1250℃ at a rate of 80 - 100℃ / h, introduce a CO2 + NH3 mixed protective gas, and hold for 10h - 12h; After diffusion annealing, cool it in the furnace at a rate of 15 - 20℃ / min to 1050℃ - 1100℃, and immediately transfer it to a high - speed forging press for multi - directional forging. Control the single - pass reduction amount to be 25 - 30% and the cumulative deformation amount ≥ 70%. During the forging process, use an infrared thermometer to monitor in real - time. Stop forging when the surface temperature of the billet drops to 950℃ - 1020℃. The obtained forged billet is air - cooled to room temperature at a cooling rate of ≥ 50℃ / s under forced air - cooling conditions; S3, Use wire - cutting technology to precisely cut the forged billet obtained in S2 into a cuboid specimen of 10mm×70mm×80mm, place it in a salt - bath furnace and heat it to 900℃ - 950℃ for 30min - 35min, and then transfer it to a constant - temperature circulating water bath for step - quenching: In the first stage, water - quench at a cooling rate of 20 - 25℃ / s to 290℃ - 310℃, and immediately transfer it to a tempering furnace and heat it to 270℃ - 310℃ at a rate of 5 - 8℃ / min and hold for 1h - 1.5h. In the second stage, use 10% NaCl aqueous solution (20 - 25℃) for rapid water - quenching, and control the transfer time within 3s, and finally cool to room temperature.

7. The preparation method of a wear-resistant alloy according to claim 6, characterized in that: In step S1, the volume ratio of CO2 to NH3 is 3:

1.

8. The preparation method of a wear-resistant alloy according to claim 6, characterized in that: In step S3, the cuboid steel is placed with its length direction perpendicular to the water surface, the distance between the steel cross - section and the water surface > 10mm, and the temperature of the quenching medium is 70℃ - 80℃.

9. The preparation method of a wear-resistant alloy according to claim 6, characterized in that: In step S3, the water quenching time is 6 to 20 s, the number of continuous water quenching times is 2 to 4 times. Each time it is taken out, the temperature needs to be detected by an infrared temperature detector, and the inclination angle of the probe measurement is 120° to 150°. The temperature of the first water quenching is ≤550 °C, and the temperature of the second water quenching is ≤400 °C. When water quenched to 330 °C to 360 °C, it is air-cooled to 270 °C to 310 °C and then put into a heating furnace for heat preservation.

10. The application of a wear-resistant alloy according to any one of claims 1-5, characterized in that: This alloy is applied to the blade of an agricultural rice harvester, specifically the moving blade of a reciprocating cutter.

Citation Information

Patent Citations

  • A high-strength and high-toughness bainitic wear-resistant steel containing carbides and its preparation method

    CN112695253B

  • High-strength high-carbon bainite wear-resistant steel and preparation method thereof

    CN118814091A